Curriculum development a guide for educators - Boyle, Bill (William F.); Charles, Marie (Los Angeles SAGE, 2016)
"Curriculum and curriculum issues are at the heart of current debates about schooling, pedagogy and learning. This book will enable practitioners, scholars and academics to understand how to re-design or to suggest changes to curriculum structure, shape and content. Grounded in theory and philosophy, the book also offers practical help in grasping this controversial area."--Page 4 of cover.
Introduction -- 1. Curriculum evolution -- 2. Developing a National curriculum: consultation -- 3. Curriculum development: case specific -- 4. Curriculum reviewing criteria: case specific -- 5. Science curriculum: case specific -- 6. Early years foundation curriculum: case specific -- 7. Balancing raising standards with a well-designed and broad curriculum -- 8. Integrating subjects and themes -- 9. Curriculum construction -- 10. Curriculum and assessment -- 11. Assessment and testing -- 12. National curriculum and summative testing.
Includes bibliographical references (pages 198-212) and index.
Keywords: Curriculum planning